The Limits of Foreign Aid Diplomacy: How Bureaucratic Design Shapes Aid Distribution. Issue 3 (20th March 2015) - Arel‐Bundock, Vincent; Atkinson, James; Potter, Rachel Augustine
Abstract : How does the institutional design of a state's bureaucracy affect foreign policy? We argue that institutions can moderate bureaucrats' incentives to act in accordance with an Executive's diplomatic preferences. Where the Executive can influence budgets or career paths, bureaucrats face incentives to adopt her diplomatic goals as their own. Where agencies are shielded from Executive influence, bureaucrats are free to act independently in a bid to enhance their autonomy and their reputation for competence. To test these expectations, we develop a new measure of bureaucratic independence for the 15 aid‐giving agencies in the US government. We analyze how independence affects foreign aid allocation patterns over the 1999–2010 period. We find that in "dependent" agencies, foreign aid flows track the diplomatic objectives of the president. In "independent" agencies, aid flows appear less responsive to presidential priorities and more responsive to indicators of need in the recipient country. Our results highlight limits on the diplomatic use of foreign aid and emphasize the importance of domestic institutional design. Our findings yield insight into a broad range of policy domains—including international finance, immigration, and the application of economic sanctions—where multiple government agencies are in charge of implementing foreign policy.